Identification of Finely Mapped Quantitative Trait Locus and Candidate Gene Mining for the Three-Seeded Pod Trait in Soybean - Li, Candong; Jiang, Hongwei; Li, Yingying; Liu, Chunyan; Qi, Zhaoming; Wu, Xiaoxia; Zhang, Zhanguo; Hu, Zhenbang; Zhu, Rongsheng; Guo, Tai; Wang, Zhixin; Zheng, Wei; et al. (Frontiers in Plant Science, 2021)
The three-seeded pod number is an important trait that positively influences soybean yield. Soybean variety with increased three-seeded pod number contributes to the seed number/plant and higher yield. The candidate genes of three-seeded pod may be the key for improving soybean yield. In this study, identification and validation of candidate genes for three-seeded pod has been carried out. Firstly, A total of 36 QTL were detected from investigation of recombinant inbred lines including 147 individuals derived from a cross between Charleston and Dongnong 594 cultivars. Five consensus QTL were integrated. Secondly, an introgressed line CSSL-182 carrying the target segment for the trait from donor parent was selected to verify the consensus QTL based on its phenotype. Thirdly, a secondary group was constructed by backcrossing with CSSL-182 and two QTL were confirmed. There was a total of 162 genes in the two QTL. The mining of candidate genes resulted in the annotation of eight genes with functions related to pod and seed set. Finally, haplotype analysis and quantitative reverse transcriptase real-time PCR were carried to verify the candidate genes. Four of these genes had different haplotypes in the resource group and the differences in phenotype were highly significant. Moreover, the differences in expression of the four genes during pod and seed development were also significant. These four genes were probably related to the development process underlying the three-seeded pod in soybean. We herein discuss the past and present studies related to three-seeded pod trait in soybean.